Comparison of Functional Outcomes Between Lumbar Interbody Fusion Surgery and Discectomy in Massive Lumbar Disc Herniation: A Retrospective Analysis. Issue 5 (June 2021) - Gupta, Anuj; Chhabra, H. S.; Nagarjuna, D.; Arora, Mohit
Study Design: Retrospective analysis. Objective: Lumbar disc herniation is one the most common condition responsible for low back and radicular pain. Although the symptoms are not proportional to the size of disc prolapse but massive disc herniation frequently needs surgical management. According to literature, the incidence of low back pain, recurrent disc herniation and segmental instability are more in discectomy whereas incidence of adjacent segment degeneration (ASD) is more after fusion surgery. There are very few studies that directly compare long-term functional outcome of both these procedures. We compared the functional outcome of both the procedures in this study. Methods: All patients of massive disc prolapse, operated at our center between 2011 to 2017, were contacted. All the patients underwent either discectomy or transforaminal lumbar interbody fusion (TLIF). Functional outcomes of all the patients were collected using visual analogue scale (VAS) (back), VAS (leg), modified Oswestry Disability Index (mODI), Sciatica Bothersomeness Index (SBI), and McNab's criterion. Various complications were also analyzed. Results: There were 144 patients in the discectomy group and 123 patients in the TLIF group. Mean duration of follow-up was 55.07 months and 51.86 months, respectively. Both the groups show no significant difference in VAS. Significant difference was seen in mODI and SBI favoring discectomy. McNab's criterion showed excellent result in 80% of patients of discectomy compared with 68% patients of TLIF. Overall complication rate in discectomy group was 11% whereas 13% in TLIF group. Conclusion: Both show good functional outcome but better in discectomy. Recurrent herniation and instability were noticed more with discectomy and ASD was more common after fusion surgeries. The choice of procedure should be individualized, and it also depends on surgical expertise, but in developing countries where resources are constrained, discectomy should be preferred.